Amino Acid Starvation and Gcn4p Regulate Adhesive Growth and FLO11 Gene Expression in Saccharomyces cerevisiae - Braus, Gerhard H. (The American Society for Cell Biology, 2003)
In baker's yeast Saccharomyces cerevisiae, cell-cell and cell-surface adhesion are required for haploid invasive growth and diploid pseudohyphal development. These morphogenetic events are induced by starvation for glucose or nitrogen and require the cell surface protein Flo11p. We show that amino acid starvation is a nutritional signal that activates adhesive growth and expression of FLO11 in both haploid and diploid strains in the presence of glucose and ammonium, known suppressors of adhesion. Starvation-induced adhesive growth requires Flo11p and is under control of Gcn2p and Gcn4p, elements of the general amino acid control system. Tpk2p and Flo8p, elements of the cAMP pathway, are also required for activation but not Ste12p and Tec1p, known targets of the mitogen-activated protein kinase cascade. Promoter analysis of FLO11 identifies one upstream activation sequence (UAS(R)) and one repression site (URS) that confer regulation by amino acid starvation. Gcn4p is not required for regulation of the UAS(R) by amino acid starvation, but seems to be indirectly required to overcome the negative effects of the URS on FLO11 transcription. In addition, Gcn4p controls expression of FLO11 by affecting two basal upstream activation sequences (UAS(B)). In summary, our study suggests that amino acid starvation is a nutritional signal that triggers a Gcn4p-controlled signaling pathway, which relieves repression of FLO11 gene expression and induces adhesive growth.